Three Decades of Butterfly–Plant Interaction Turnover Explained by Climate and Species Loss - Pau Colom; Constantí Stefanescu; Jordi Corbera; Amparo Lázaro (Ecology Letters, 2026)
Understanding the mechanisms behind interaction turnover over long‐term periods is essential to predict how ecological networks respond to global change. We used a high‐resolution dataset of butterfly–plant interactions spanning 13–29 years in seven Mediterranean communities to assess how climate fluctuations and community shifts shape interaction turnover and its components—species turnover and rewiring. Rewiring contributed the most to interaction turnover, but its relative importance declined over time as species loss reduced the pool of shared partners between years. Consequently, species turnover became increasingly influential, even though communities shifted toward butterfly species with generalist traits that promote rewiring. Nevertheless, rewiring intensified in years with stronger temperature fluctuations, when populations experienced greater shifts in phenology and abundance and were more likely to rewire. In the context of biodiversity loss, species turnover increasingly governs interaction dynamics, while the short‐term flexibility provided by rewiring may collapse as communities become impoverished.